Critical Remarks on the Law of Protection and Improvement of the Environment in the Kurdistan Region - Iraq No. (8) of (2008) - سەنگەر داوود محمد , (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
Since the beginning of creation, man has been concerned about protecting the environment with all its various components and components as the natural and fundamental center of his life. The scientific and technological revolution, the misuse of biological resources and the increase in the number of wars and armed conflicts have exacerbated the problems of environmental pollution. Fate of living things, which led to the international and internal efforts and efforts to address environmental pollution and to provide legal cover and regulation for the protection and improvement of the environment? This resulted in the attention of the internal legislator and the enactment of special legislation to protect and improve the environment and the development of texts and rules. Provisions and the establishment of regulatory frameworks to address environmental risks and reduce pollution and emphasize the human right to live in a clean and healthy. In line with these efforts and keeping pace with the internal legislative interest to protect and improve the environment, the legislator in the Kurdistan Region of Iraq enacted the law for the protection and improvement of the environment in the Kurdistan Region of Iraq No. (8) for the year 2008. The gaps in the law of protection and improvement of the environment in the region, the prominent role in our selection of the subject of our research, the is a serious attempt to shed light on the gaps and deficiencies and shortcomings and legislative limitations contained in the law of protection and improvement of the environment in the Kurdistan Region of Iraq No. (8)for the year 2008, in preparation for the presentation of appropriate proposals to address these gaps.